Heralded Generation of Vectorially Structured Photons With a High Purity - Wu, Hai-Jun; Yu, Bing-Shi; Zhu, Zhi-Han; Rosales-Guzmán, Carmelo; Zhou, Zhi-Yuan; Ding, Dong-Sheng; Gao, Wei; Shi, Bao-Sen (Frontiers in Physics, 2021)
Engineering vector spatial modes of photons is an important approach for manipulating high-dimension photonic states in various quantum optical experiments. In this work, we demonstrate generation of heralded single photons with well-defined vector spatial modes by using a self-locking polarizing interferometer comprising a spatial light modulator. Specifically, it is shown that, by carefully tailoring and compensating spatial and temporal amplitudes of manipulated photons, one can exactly convert ultrafast single photons into desired spin-orbit states with extremely high purity. This compact and robust device provides a versatile way for not only generation, but also manipulation and characterization of arbitrary photonic spin-orbit states.